1990
DOI: 10.1063/1.344944
|View full text |Cite
|
Sign up to set email alerts
|

Surface mechanisms in O2 and SF6 microwave plasma etching of polymers

Abstract: Photoresist etching mechanisms in O2 abd SF6 microwave plasmas are investigated using x-ray photoelectron spectroscopy (XPS) and etch rate measurements. Experiments are performed in a microwave multipolar plasma using an electron cyclotron resonance at 2.45 GHz and independent rf biasing at 13.56 MHz. The photoresist etch rates are studied as a function of the parameters of the plasma polymer interaction. As in an O2 plasma, the etch rate in SF6 exhibits a two-step evolution with ion energy as well as a monola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 22 publications
0
26
0
2
Order By: Relevance
“…The resist was etched in a distributed electron cyclotron resonance ͑DECR͒ etcher using O 2 , SF 6 , and Ar plasmas. 13,14 In contrast to polyimide, the degradation was not confined to the surface but extended into the bulk.…”
Section: A Analysis Of the Resist Degradation Phenomenon Occurring Dmentioning
confidence: 86%
See 2 more Smart Citations
“…The resist was etched in a distributed electron cyclotron resonance ͑DECR͒ etcher using O 2 , SF 6 , and Ar plasmas. 13,14 In contrast to polyimide, the degradation was not confined to the surface but extended into the bulk.…”
Section: A Analysis Of the Resist Degradation Phenomenon Occurring Dmentioning
confidence: 86%
“…In oxygen or fluorine based plasmas, the degradation phenomenon has also been observed. 13,14 On the other hand, in reactive plasmas, the degradation results from the competition between the formation ͑due to ion bombardment͒ and etching of the graphitized film ͑by reactive species͒. The surface degradation of the resist and its thermal extension into the bulk can be avoided if the carbonaceous graphitized layer, induced by ion bombardment, is stripped by the chemically active species in the plasma as it forms.…”
Section: A Analysis Of the Resist Degradation Phenomenon Occurring Dmentioning
confidence: 98%
See 1 more Smart Citation
“…Detailed mechanisms to describe their formation remain unclear. [13,14] The observation of the even stronger greenhouse gas SF 5 CF 3 , chemically related to SF 6 , in stratospheric air samples has further raised questions of the atmospheric consequence of these species. [15] At present the molar ratio of SF 5 CF 3 relative to SF 6 amounts to about 4 %.…”
mentioning
confidence: 98%
“…The main species of such plasmas have been delineated by Picard, who indicated three kinds of energetic species reacting on the polymer surface: neutral molecules, ions, and an electron density [23]. The studies of Joubert and Frank suggested that the reaction mechanism at the material surface in a plasma system was a two-step process for energetic species of fluorine reacting with the polymer surface [24,25].…”
Section: Introductionmentioning
confidence: 99%